The effect of balance on improving the accuracy of aims in players football (cubs) - Mazari, F.; Bounadj, M.; Hamani, I. (The Russian Journal of Physical Education and Sport, 2018)
Annotation. The aim of this study is to propose a training program for the development of the equilibrium character of football players. This topic was chosen in order to highlight the importance of the proposed training programs based on the sound scientific foundations in upgrading the skill level of the players. Materials. The study also focused on highlighting the role of the trainer in selecting the best training programs used to reach the required levels and learning about the reality of the preparation and composition of the small football teams in the state of Bouira and the detection of their strengths and weaknesses. Research methods. The sample was deliberately selected and represented 36 players divided into two groups (experimental) 18 players from the amateur sports club of the municipality of Qadiriya The training program and the group (witness) were 18 players from the Federation of Ahdhariyah, which was trained according to the regular program. It was based on tribal and remote tests as a tool for study. The researcher relied on the following statistical means: The statistical package program (spss18) was based on both the arithmetic mean, the standard deviation, the Pearson simple torsion factor, Pearson correlation coefficient (T), the independent sample samples, and the TT. Results. The results indicate that the training program proposed by the group (experimental) of 18 players from the amateur sports club of the municipality of Qadiriyah affected the balance and accuracy of correction. It achieved the validity of all hypotheses by the researcher. The first hypothesis - the training program improves stability. For the second hypothesis - the training program improves motor balance. Hypothesis three - the training program improves the accuracy of the aims. Through all these findings and conclusions, we have achieved the validity of the general hypothesis that balance has an effect on improving the correctness of football players. Conclusion. The results were greater than those between the pre and post tests in this group in the foot-correction tests (rope test, interlocking rectangles test). They were intended to measure the accuracy of the foot correction. The group also obtained significant differences in the tests of the equilibrium power measurement. The group obtained values indicating significant differences and improvement. The results demonstrate the need to improve the balance correction, which opens the way for complementary studies as a starting point for a broader study.